A two-step parameter estimation method for estimating soil thermal properties of coaxial ground heat exchangers. (November 2021) - Wang, Changlong; Fang, Han; Lu, Jinli; Sun, Yanhong; Zhang, Pengyuan; Wang, Xin
Highlights: The correlation between (ρc)s and GHE performance for early 10 hours is stronger than that after 10 hours. Long-time TRT data lead to more accurate estimation of ks than early-time TRT data. Early-time TRT data lead to more accurate estimation of (ρc)s than long-time TRT data. Soil thermal properties estimated by the proposed method have higher precision than those by another method. Abstract: Soil thermal properties are important parameters to design the coaxial ground heat exchanger (GHE). This paper adopts an accurate semi-analytical model to analyse the sensitivities of soil thermal properties on the performance and parameter estimation of coaxial GHE, and then proposes a two-step parameter estimation method by using early-time thermal response test (TRT) data to estimate the soil volumetric heat capacity and using long-time TRT data to estimate the soil thermal conductivity, and finally verifies the proposed method by comparison with another parameter estimation method and experimental data. The main findings are as follows: there is strong correlation between soil thermal conductivity and coaxial GHE performance, and the correlation between soil volumetric heat capacity and coaxial GHE performance for the early 10 hours is stronger than that after 10 hours; long-time TRT data can lead to more accurate estimation of soil thermal conductivity than early-time TRT data, and early-time TRT data can lead to more accurate estimation of soil volumetric heat capacity than long-time TRT data; the soil thermal properties (especially volumetric heat capacity) estimated by the proposed method have higher precision than those by another method, which uses long-time TRT data to estimate the soil thermal properties.